Hubungan Sikap dan Motivasi Perawat dalam Pelaksanaan Pendidikan Pasien dan Keluarga terhadap Pencegahan Kekambuhan Pasien Gangguan Jiwa - Dwi Kartika Pebrianti (Jurnal Akademika Baiturrahim Jambi, 2021)
One of the causes of the high recurrence rate in mental illness patients is the lack of understanding of the patient and their family in caring for patients at home after returning from the mental hospital. This understanding is obtained through the educational process provided by health workers, one of which is a nurse. Health education for patients and their families is very necessary for patient independence after returning home, especially for patients with mental disorders. This study aims to determine the relationship between attitudes and motivation of nurses in implementing patient and family education in mental hospitals. This research used quantitative methods with cross sectional approach. The sample size is 117 nurses. The sampling technique used was proportional random sampling technique. Place of research in the inpatient room of the Jambi Province Mental Hospital. The bivariate analysis found that there was a nurse motivation (0.03) with the performance of nurses in providing health education to patients and their families. While the data analysis attitude variable has no relationship (p-value: 0.302). It is hoped that nurses as the spearhead of service at RSJD Jambi Province can improve their role and performance in providing health education which contributes to increasing the health status of patients reducing the risk of recurrence due to a lack of understanding of patients and families in caring for patients while at home